(untitled) (Bangladesh Pharmaceutical Journal, 2017)
In modern Human Resource Management (HRM) practice, the concept of Quality of Work Life (QWL) is relatively a new strategy for employee retention. The idea of QWL is developed upon the increasing importance of reducing employee turnover rate in a highly competitive market. Better QWL practice in sales and marketing oriented companies is inevitable to ensure employee productivity and therefore needs to be studied in detail. The core objective of the study was to measure the impact of QWL variables on the lives of Marketing Representatives (MR) of pharmaceutical companies. First, the variables influencing QWL are elaborated with the help of extensive literature review. Then this study tried to identify the current scenario of QWL Practices in ten renowned pharmaceutical companies through a survey of 112 MRs. This was supplemented with in-depth interviews of HR executives of three different companies. The study discovered job stress as a high priority indicator of QWL. The research also revealed organizational atmosphere based on fairness, experience sharing culture, employee suggestion scheme, opportunity to use skill and satisfactory reward system as influential determinants of QWL. This paper recommends the installation of QWL practices in other pharmaceutical companies with few short and long-term suggestions. There is room for conceptualizing and actualizing standard QWL practice in the Bangladeshi pharmaceutical companies. An initiative like this one will encourage discussion and debates in applying much needed QWL practices in other sectors. Bangladesh Pharmaceutical Journal 20(1): 46-53, 2017